Virtual Technology in Museums and Art Galleries Business Practice – The Empirical Research - Marija Dragicevic; Antonija Bagarić (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Contemporary museums are much more than places devoted to the placement and the exhibition of collections and art works. One of the keys to the general public approach is the use of new technologies and different structuring according to the clients profile and preferences. Virtual reality (VR) is probably one of the most potentially effective technologies for this purpose. The main purpose of implementation of 3D technology in museums and art galleries business practice is to create system which museum visitors can offer an entertaining, informative and enjoyable experience. This paper presents a results of study that has been undertaken in order to explore use of virtual technology in museums and art galleries in the area of Dubrovnik as the well-known tourist destination, with rich cultural heritage.
Keywords: 650; art galleries; Croatia; Dubrovnik; museums; virtual technology